Decision Making and Robust Optimization for Medicines Shortages in Pharmaceutical Supply Chains - Miranda, João Luís de; Nagy, Mariana; Casquilho, Miguel (Advanced Studies in Multi-Criteria Decision Making, 2020)
The landscape and the factors affecting the operations of the pharmaceutical supply chains (PharmSC) with specific concern on medicines manufacturing disruptions are described, as are the main topics on "Medicines Shortages" within the homonymous COST Action (CA15105). The chapter deals with multi-criteria decision-making (MCDM) tools to address the suppliers selection problem and curb shortages by applying robust optimization (RO) models for the PharmSC design and planning, dealing with uncertainty and risk, and coping with computational issues. Definitions and goals are updated, adjusting the PharmSC approaches and models, in a way to enlighten the costing and performance indexes of shortages. Relevant topics are also integrated, namely, the provisions and procurement disruptions, the clinical-pharmacological needs, and the shortages impact. Thereafter, a real situation for deciding on the supplier bid within a PharmSC is addressed. On considering the referred criteria set, the decisional matrix is built and four different methods with the associated software are applied: (i) the simple additive model; (ii) the TOPSIS model; (iii) the "e" Fuzzy model; and (iv) the ELECTRE model. Through a hierarchic process, the top of alternatives is built, and the decisional process ends by assigning one of the bidder supplier companies. As the resulting hierarchies are only slightly different, a comparative analysis that addresses the deviations amplitude, the best alternative, and the least preferred alternative is performed. This chapter presents adequate multi-criteria decision aiding tools and robust optimizations to the medicines shortages within the Pharmaceutical Supply Chains (PharmSC) framework: the robust modeling for the design and scheduling of batch processes is revisited, so is the PharmSC's problem structuring. It discusses the multiperiod robust model and the economic and financial estimators for medicines shortages. The chapter introduces the COST Action on "Medicines Shortages", and describes the main factors affecting the PharmSC operations with specific concern on manufacturing disruptions. Finance and information fluxes are also focused when updating the PharmSC techniques, as well as the related decision making methodologies. Additional data can be used to better detail the decision procedure, such as the characteristics within the attributes and the related indicators. The study of optimization cases and models from the literature allowed a detailed overview and permitted to conjugate realistic subjects both in formulation and solution procedures.